Knowledge of vocabulary and students' written communicative competen ce in English at `O' level in selected Kampala Secondary Schools - Beigaruraho-Bazaare, Angeline (Kampala: Makerere University, 1993)
Thesis (M. Education) - Makerere University, 1993.
Includes bibliographical references (p.67-75)
Keywords: English language -- Study and teaching (Secondary) -- Uganda -- Kamp ala District